2010
DOI: 10.1021/la9042809
|View full text |Cite
|
Sign up to set email alerts
|

Ce:YAG Nanoparticles Embedded in a PMMA Matrix: Preparation and Characterization

Abstract: A Ce:YAG-poly(methyl methacrylate) composite was prepared using in situ polymerization by embedding the Ce:YAG nanopowder in a blend of methyl methacrylate (MMA) and 2-methacrylic acid (MAA) monomers and activating the photopolymerization using a radical initiator. The obtained nanocomposite was yellow and transparent. Its characterization was performed using transmission electron microscopy, small angle X-ray scattering, (13)C cross-polarization magic-angle spinning nuclear magnetic resonance, and photolumine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 36 publications
4
48
0
Order By: Relevance
“…These variations can account for specific interactions between the polymer and the surfaces of the Ce:YAG particles. In fact, in agreement with a previous finding [9,10], an electron donor-acceptor interaction between the carboxyl oxygen lone pair and the surface yttrium or cerium ions could take place. This specific interaction can account for the observed variations in the relaxation time due to the retrieval of electrons along the polymer chain.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These variations can account for specific interactions between the polymer and the surfaces of the Ce:YAG particles. In fact, in agreement with a previous finding [9,10], an electron donor-acceptor interaction between the carboxyl oxygen lone pair and the surface yttrium or cerium ions could take place. This specific interaction can account for the observed variations in the relaxation time due to the retrieval of electrons along the polymer chain.…”
Section: Resultssupporting
confidence: 92%
“…Recently, some of us demonstrated that polymeric composites of polymetylmethacrylate (PMMA) containing Ce:YAG is an ideal yellow light emitter complementary to a blue light to the realization of a white LED on a large scale [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposite materials, based on a polymer matrix and inorganic nanoparticle fillers, have drawn considerable attention in recent years, due to improvements in various properties including electrical, thermal, optical and other mechanical properties [1][2][3][4][5]. Poly(methyl methacrylate)/zirconia (PMMA-ZrO 2 ) is one of the most important nanocomposites that has been applied for the increasing demands of optical waveguides, ophthalmic lenses, antireflection coatings and adhesives for optical components.…”
Section: Introductionmentioning
confidence: 99%
“…This will not only immobilize the polymer chains but also the free radicals that take part in the degradation process. This stronger interaction is probably also the result of a local structured distribution of PMMA chains around the Ce:YAG nanoparticles [10]. The second heating DSC curve of PMMA-CoHCF ( Figure 5) shows a shift in T g to a higher temperature by about 6°C.…”
Section: Resultsmentioning
confidence: 96%
“…Ce:YAG, combined with GaN blue light emitting diodes (LED), is used for white light solid-state LED. In previous work it was described how the presence of filler (Ce:YAG) in the PMMA matrix can cause an organization of the structure into a lamellar shape around the particles [10]. This organization could influence the macro features of the composites.…”
Section: Introductionmentioning
confidence: 99%